Coolidge Corner, general view of an apartment house, Brookline, Massachusetts. - Floyd, Margaret Henderson. (Tufts University. Tisch Library., 2015)
General exterior view of an apartment building in Coolidge Corner. Coolidge Corner is a neighborhood of Brookline, Massachusetts, centered around the intersection of Beacon Street and Harvard Street. The neighborhood takes its name from the Coolidge brothers' general store. (Source: Wikipedia).; Caption on image: Coolidge Corner (2) Ext, gen. view w/Moviehouse Walking Tour.; Binder Number 4. Pocket Number: 16.; Format: 35mm col. slide.; Slide created date: This date is approximate. 1970.; Apply to the DCA for access to the physical slides.